Importancia de la excelencia docente de posgrados: un análisis de la evaluación docente y su impacto en la calidad educativa en UNIANDES - Padilla Uribe, Jaime Santiago (2025)
Educational quality in graduate programs at Universidad Regional Autónoma de los Andes “Uniandes” is linked to teaching excellence, which becomes a key factor for the integral development of students and the consolidation of advanced professional competencies. This article evaluated the impact of teaching evaluation as a fundamental tool to guarantee educational quality, highlighting the challenges and opportunities in the context of graduate programs at Uniandes. Committed to the continuous improvement of its programs, it has implemented systematic teacher evaluation processes as a strategy to ensure academic excellence and meet the expectations of the educational community. In this context, structured questionnaires were used for data collection to obtain perceptions and opinions of the participants, which are analyzed through descriptive and inferential statistical methods in order to evaluate the relationship between teacher evaluation and educational quality. As for the group involved in the data collection, it is found that the teachers and students of the graduate programs of Uniandes between the months of September and October 2024, take into account internal teachers and occasional guests. This analysis was based on a review of teaching evaluation systems, integrating qualitative and quantitative data obtained through surveys, interviews and review of performance indicators. The guidelines of the Council for Quality Assurance in Higher Education and international best practices in university teaching evaluation were also considered.